Current concepts of percutaneous balloon kyphoplasty for the treatment of osteoporotic vertebral compression fractures: Evidence-based review - Ming-Kai Hsieh (Biomedical Journal, 2013)
Vertebral compression fractures constitute a major health care problem, not only because of their high incidence but also due to both direct and indirect consequences on health-related quality of life and health care expenditures. The mainstay of management for symptomatic vertebral compression fractures is targeted medical therapy, including analgesics, bed rest, external fixation, and rehabilitation. However, anti-inflammatory drugs and certain types of analgesics can be poorly tolerated by elderly patients, and surgical fixation often fails due to the poor quality of osteoporotic bone. Balloon kyphoplasty and vertebroplasty are two minimally invasive percutaneous surgical approaches that have recently been developed for the management of symptomatic vertebral compression fractures. The purpose of this study was to perform a comprehensive review of the literature and conduct a meta-analysis to compare clinical outcomes of pain relief and function, radiographic outcomes of the restoration of anterior vertebral height and kyphotic angles, and subsequent complications associated with these two techniques.